Succinate and the shortcut to the cure of metformin-induced lactic acidosis - Protti, Alessandro (Intensive Care Med Exp, 2018)
Inhibition of the respiratory chain complex I plays a key role in the pathogenesis of metformin-induced lactic acidosis. In a work recently published in this journal, a novel cell-permeable succinate prodrug (NV118) increased in vitro mitochondrial oxygen consumption coupled with energy production and decreased lactate production in intact human platelets intoxicated with metformin. This result was interpreted in light of a “bypass” strategy. NV118 entered platelets and released succinate in their cytoplasm; succinate in turn donated electrons to complex II and thus reactivated the flow of electrons to the distal part of the respiratory chain independent of complex I. Herein, I will (1) comment on these findings; (2) highlight the potential therapeutic application of succinate in other critical conditions accompanied by complex I inhibition, including sepsis, traumatic brain injury, and inherited neurological disorders; and (3) examine the most important issues that remain to be solved to transfer these observations to the bedside.